Dogmática de los derechos fundamentales y transformaciones del sistema constitucional - Pérez Luño, Antonio Enrique (Teoría y Realidad Constitucional, 2007)
This essay studies the aspects that have contributed to the crisis of the theory of the fundamental rights inspired by the juridical positivism. The legal systems and, in particular, their normative sources, have been directly affected by the phenomenon of prevail of the state’s monopoly of creation of juridical norms. A deep change has been verified inside the legal systems that has been translated into a triple displacement: from the unit to the pluralism; from the fullness to the jurisdictional opening; and from the coherence to the argument. In this work these new phenomena and their repercussion are analyzed for the freedoms.